Kyrgyz Republic : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This report has identified the following major issues in the public sector financial accountability of the Kyrgyz Republic: 1) weak internal controls in several areas such as treasury, budget implementation, procurement, human resources, accounting and reporting as evidenced by large amounts o f illegal unintended expenditures, embezzlements and other financial offences reported by the external auditor; 2) weak cash management as the treasury cash rations on a day-to-day basis, which creates uncertainty for budget institutions in implementing their plans; 3) absence of a legal basis for internal audit in the public sector; 4) weak capacity in the C A for carrying out effective financial audits and focusing attention on the basis of risk assessment; 5) weak capacity in line ministries to undertake systematic budgeting exercise; 6) budget monitoring is limited to monitoring of fiscal targets as little attention is paid to assessment of program effectiveness; 6) lack of systematic management accounting and weak capacity in departmental management to absorb and use management accounting data in decision making and management processes; 7) weak capacity in the parliamentary committees to provide effective legislative oversight over the executive; and 8) inadequate accountability arrangements for public enterprises. Key Recommendations offered in the short term involve: 1) strengthening internal controls and the treasury cash management function; 2) establishing daily reconciliation of consolidated district treasury payment requests; 3) reconciling daily revenue collections; and 4) granting authority to the Chamber of Accounts (CA) to perform interim post audits. In the long term the Government should: 1) enact the Law on Public Sector Internal Audit and build internal audit capacity; 2) establish effective internal audit structures in the line ministries; 3) prepare rules and methodology for conducting internal audits in the public sector; 4) provide extensive training; 5) require internal auditors to carry out detailed assessments of internal controls; 6) require the CA to certify the year-end financial statements of the government; 7) make the process of appointment of the Chairman of the CA transparent; 8) discontinue the special means provisions; and 9) clearly define the accountability of public enterprises.